Assessing the relationship between climate, food security and conflict in Ethiopia and in the Central American Dry Corridor (CADC). Quantitative analysis on the impact of climate variability on conflict in Ethiopia and in the CADC countries. Appendix - Pacillo, Grazia; Carneiro, Bia; Resce, Giuliano; Ruscica, Giosuè; Craparo, Alessandro Carmelo William; Basel, Ashleigh Megan; Ramírez Villegas, Julián Armando; Achicanoy Estrella, Harold Armando; Villa, Victor; Krendelsberger, Alexandra; Läderach, Peter R.D. (CGIAR FOCUS Climate Security, 2021)
This appendix describes more in details the methods used in the WFP - CGIAR project "Assessing the relationship between climate, food security and conflict in Ethiopia and in the Central American Dry Corridor (CADC). Quantitative analysis on the impact of climate variability on conflict in Ethiopia and in the CADC countries." In this study, we investigate the climate-food security-conflict nexus in Ethiopia and the CADC (Guatemala, El Salvador, Nicaragua, Honduras). Both Ethiopia and the CADC are hotspots of high climate variabilities, high political insecurity, and conflicts and widespread food and nutrition insecurities across their populations.